2005
DOI: 10.1091/mbc.e05-01-0072
|View full text |Cite
|
Sign up to set email alerts
|

p115 Interacts with the GLUT4 Vesicle Protein, IRAP, and Plays a Critical Role in Insulin-stimulated GLUT4 Translocation

Abstract: Insulin-regulated aminopeptidase (IRAP) is an abundant cargo protein of Glut4 storage vesicles (GSVs) that traffics to and from the plasma membrane in response to insulin. We used the amino terminus cytoplasmic domain of IRAP, residues 1-109, as an affinity reagent to identify cytosolic proteins that might be involved in GSV trafficking. In this way, we identified p115, a peripheral membrane protein known to be involved in membrane trafficking. In murine adipocytes, we determined that p115 was localized to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 50 publications
3
77
0
Order By: Relevance
“…We therefore wondered whether there could also be a pre-TGN (Golgi cisternae) decision step that directs GLUT4 toward a specific pathway required for appropriate TGN sorting. While our study was in progress Hosaka et al (2005) provided further support for this speculation by demonstrated that the p115 golgin protein could directly bind to IRAP (Hosaka et al, 2005). Regardless, we elected to examine the role of golgin-160 on the trafficking of GLUT4 due to the observations that golgin-160 can directly interact with the protein PIST/GOPC/CAL/ FIG (Hicks and Machamer, 2005).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We therefore wondered whether there could also be a pre-TGN (Golgi cisternae) decision step that directs GLUT4 toward a specific pathway required for appropriate TGN sorting. While our study was in progress Hosaka et al (2005) provided further support for this speculation by demonstrated that the p115 golgin protein could directly bind to IRAP (Hosaka et al, 2005). Regardless, we elected to examine the role of golgin-160 on the trafficking of GLUT4 due to the observations that golgin-160 can directly interact with the protein PIST/GOPC/CAL/ FIG (Hicks and Machamer, 2005).…”
Section: Discussionmentioning
confidence: 87%
“…In support of this model, the TGN cargo adaptor Golgi-localized, ␄-earcontaining ARF-binding protein (GGA) is required for the initial entry of GLUT4 from the TGN into the insulin-responsive compartment (Watson et al, 2004). More recently, the expression of an amino-terminal deletion mutant of the Golgi tethering protein, p115 was found to inhibit insulinstimulated GLUT4 translocation to the plasma membrane, suggesting a role for p115 in the intracellular tethering of GLUT4 (Hosaka et al, 2005).p115 is one member of a large golgin family of Golgilocalized proteins. These proteins have been implicated in the maintenance of proper Golgi structure and function (Barr et al, 2003).…”
mentioning
confidence: 95%
“…The regulated trafficking of IRAP depends on the cytosolic domain of the enzyme, which has been shown to interact with several proteins involved in vesicle formation or in cytoskeleton remodeling, such as the golgin p115 18 , vimentin 19 and FHOS (formin homologue overexpressed in the spleen, also called FHOD1) 20 . Whether these proteins and their interaction with the cytosolic domain of IRAP play a role in the trafficking of IRAP + endosomes is not known.…”
mentioning
confidence: 99%
“…Akt antibody and pAkt (Ser473) antibody were from Cell Signaling Technology (Beverly, MA). GLUT4 antibody was raised and purified as described previously (19). HRP-conjugated IgG second antibodies were purchased from Life Technologies (Carlsbad, CA).…”
Section: Antibodiesmentioning
confidence: 99%
“…3T3-L1 fibroblasts were induced to differentiate as described previously with minor modification (19). Briefly, 3T3-L1 fibroblasts were cultured in 15 cm dishes for electroporation with DMEM containing 4.5 g/l glucose, L-glutamine and 10% calf serum.…”
Section: Cell Culturementioning
confidence: 99%